Liver steatosis, metabolically healthy obesity and ten-year cardiovascular disease risk: results from a population based cohort study. (14th October 2021) - Kouvari, M; Chrysohoou, C; Georgousopoulou, E; Skoumas, J; Pitsavos, C; Panagiotakos, D B; Mantzoros, C S
Abstract: Background/Introduction: Inclusion of non-alcoholic fatty liver disease (NAFLD) as a component of metabolic syndrome (MetS) and/or a criterion for defining metabolically healthy vs. unhealthy obese (MHO vs MUO) status remains to be decided. Purpose: The present work evaluated the role of NAFLD at baseline in the transition of MHO to MUO status, and its role in predicting cardiovascular disease (CVD) incidence ten years later. Methods: A prospective longitudinal study was performed between 2001 and 2012 studying 1, 514 (49·8%) men and 1, 528 (50.2%) women (>18 years old) free of CVD at baseline and residing in the greater Athens area, Greece. Follow-up assessment of first fatal/non fatal CVD event (2011–2012) was achieved in n=2, 020 participants (n=317 cases). Healthy metabolic status was defined as absence of all NCEP ATP III (2005) metabolic syndrome components. NAFLD was defined according to validated liver steatosis indices. Results: Among obese participants, MHO prevalence was 9.8% (n=277). Only half of the MHO subjects retained their metabolically healthy status one decade later. NAFLD was an important predictor of this transition; MHO participants with NAFLD at baseline had about two times higher odds to develop unhealthy metabolic status compared with their non-NAFLD counterparts. Subsequently, MHO status accompanied by NAFLD was associated with increased CVD risk (Hazard Ratio=2.90 95%Confidence Interval (1.35, 5.40)) in contrast to their non-NAFLD MHO counterparts. C-statistics revealed that NAFLD significantly increased the discriminative ability of the standardly defined metabolic status (p for C-index change=0.002), yet in the total sample its contribution to the model seemed to be similar with the common metric of central obesity i.e. waist circumference (CNAFLD=0.711 vs. Cwc=0.710). When the analysis was restricted to the obese subset, it was revealed that the discriminative ability of the model adjusted for NAFLD was significantly higher compared with the one adjusted for waist circumference (CNAFLD=0.719 vs. Cwc=0.702). Conclusions: Taking under consideration NAFLD – via validated indices – in the clinical assessment of an apparently healthy obese individual contributes to better defining future risk of conversion to metabolically unhealthy obesity and future cardiometabolic risk. Funding Acknowledgement: Type of funding sources: None.